ANTIBIOTIC RESISTANCE OF CAUSES OF URINARY TRACT INFECTIONS IN PATIENTS AT THE PUBLIC HEALTH INSTITUTE KRAGUJEVAC - Lazarevic, Jelena; Nikolic, Biljana; Malesevic, Zoranka; Ninkovic, Violeta (HEALTH CARE, 2022)
Introduction/Aim: Urinary tract infections are one of the most common infections in primary healthcare. The aim of this study was the microbiological analysis of urine of infirmary patients at the Institute of Public Health in Kragujevac during the six-month period (1st November 2020 – 30th April 2021). Methods: Causes of urinary tract infections were identified retrospectively, according to the collected data, and their sensitivity to antibiotics was determined with the help of antibiogram method.Results: A six-month analysis of urine samples of infirmary patients included 4809 urine samples. Of all analyzed samples, 1218 (25.3%) were positive to pathogens. The commonest urinary tract pathogens in the examined period were the following: Escherichia coli 842 (69.1%), Klebsiella spp. 252 (20.7%), Pseudomonas aeruginosa 71 (5.8%) and Enterococcus group 53 (4.4%). E. coli was more frequent in women (82.7%), while Pseudomonas aeruginosa was more frequent in men (76.1%). Klebsiella spp. and Enterococcus spp. were almost equally present in men and women. First-choice drugs in the treatment of urinary infections would be the following: for E. coli amikacin (aminoglycoside) and fosfomycin, and for Klebsiella spp. meropenem (carbapenem) and also amikacin. As far as P. aeruginosa is concerned, meropenem was shown to be the most efficient, as well as the penicillin antibiotic piperacillin-tazobactam.Conclusion: Considering that uropathogens possess mechanisms for the development of resistance, the treatment should include antibiotics depending on the results of antibiogram.
Keywords: uropathogens, antibiotic resistance, antibiogram